Association between IL‐1R2 polymorphisms and lung cancer risk in the Chinese Han population: A case–control study. Issue 5 (20th March 2019) - Wang, Chaoying; Zhang, Chengsheng; Xu, Junnv; Li, Yongfu; Wang, Jie; Liu, Hui; Liu, Yueli; Chen, Zhong; Lin, Haifeng
Abstract: Background: Interleukin‐1 receptor 2 (IL‐1R2), as an anti‐inflammatory cytokine, is involved in the pathogenesis and progression of lung cancer. However, the role of IL‐1R2 polymorphisms in patients with lung cancer has yet to be fully elucidated. Methods: Six single‐nucleotide polymorphisms (SNPs) in IL‐1R2 were genotyped in 259 patients and 346 healthy controls. We used the chi‐squared test, genetic model analysis, Haploview analysis, and multifactor dimensionality reduction (MDR) to evaluate the potential association between IL‐1R2 polymorphisms and lung cancer susceptibility. Bioinformatics analyses were conducted to analyze the expression level of IL‐1R2 and its association with the overall survival of lung cancer. Results: Our results found that rs3218977‐GG was associated with a decreased risk of lung cancer (odds ratio [OR] = 0.39; 95% confidence interval [CI]: 0.17–0.87; p = 0.023), and rs2072472 had a significant risk‐increasing effect in the dominant model (AG + GG vs. AA: OR = 1.54; 95% CI: 1.09–2.20; p = 0.015). The MDR model also revealed that rs2072472 is the most influential risk factor of lung cancer (testing accuracy = 0.543; cross‐validation consistency = 10/10; p = 0.032). In addition, our results indicated that the IL‐1R2 mRNA level was downregulated in lung cancer patients, whereas the high expression of IL‐1R2 was related to a poor prognosis in lung cancer. Conclusions: Our results suggest that genetic variants of IL‐1R2 may play a role in lung cancer susceptibility. Further population and functional validations of our findings are warranted. Abstract : To determine the potential association between IL‐1R2 polymorphisms and lung cancer susceptibility, six single‐nucleotide polymorphisms (SNPs) in IL‐1R2 were genotyped in 259 patients and 346 healthy controls. We used the chi‐squared test, genetic model analysis, Haploview analysis, and multifactor dimensionality reduction (MDR). Bioinformatics analyses were conducted to analyze the expression level of IL‐1R2 and its association with the overall survival of lung cancer. Our results found that rs3218977‐GG was associated with a decreased risk of lung cancer (odds ratio [OR] = 0.39; 95% confidence interval [CI]: 0.17–0.87; p = 0.023), and rs2072472 had a significant risk‐increasing effect in the dominant model (AG + GG vs. AA: OR = 1.54; 95% CI: 1.09–2.20; p = 0.015).